2021
DOI: 10.1007/s13205-021-02749-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of novel coronavirus disease (COVID-19): based on genomic structure, phylogeny, current shreds of evidence, candidate vaccines, and drug repurposing

Abstract: Coronavirus disease (COVID-19) pandemic is instigated by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As of March 13, 2021, more than 118.9 million cases were infected with COVID-19 worldwide. SARS-CoV-2 is a positive-sense single-stranded RNA beta-CoV. Most COVID-19 infected individuals recover within 1–3 weeks. Nevertheless, approximately 5% of patients develop acute respiratory distress syndrome and other systemic complications, leading to death. Structural genetic analyses of SARS-CoV-2 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 119 publications
(132 reference statements)
0
11
0
Order By: Relevance
“…Therefore, we analysed genomic sequence of SARS-CoV2 strains from different countries to understand the viral origin and its evolution during the pandemic. In this study, we observed that SNP occurrence is not random, but it is more common in the genes, which are critical for virus [ 38 ]. In Saudi Arabian SARS-CoV2 strain (EPI_ISL_678216), 16 variations were observed as compared to the wuhan-hu1 SARS-CoV2 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we analysed genomic sequence of SARS-CoV2 strains from different countries to understand the viral origin and its evolution during the pandemic. In this study, we observed that SNP occurrence is not random, but it is more common in the genes, which are critical for virus [ 38 ]. In Saudi Arabian SARS-CoV2 strain (EPI_ISL_678216), 16 variations were observed as compared to the wuhan-hu1 SARS-CoV2 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its richness, the whole virus particle serves as an antigenic target for vaccines and contains all structural proteins namely S, N, M and E proteins [28,17] . Live-attenuated virus vaccines can also generate nonstructural and accessory proteins in vivo [29] . It has been reported that, CoronaVac vaccines can induce broader antibody and T-cell responses than the above-mentioned vaccines, which are based on a single protein or protein fragments [26,30] .…”
Section: Types Of Covid-19 Vaccinesmentioning
confidence: 99%
“…If possible, make an emergency call to a nearby hospital care center so that suffering person can be treated as soon as possible. Some people, who have COVID-19 virus, whether or not they sought hospital care, continue to suffer with symptoms like fatigue, respiratory problem and neurological signs (20)(21)(22).…”
Section: Clinical Manifestationmentioning
confidence: 99%